Alternative futures of food consumption in Tehran metropolis - Farshid Azizkhani; Mohammad Rahim Eivazi; Majid mokhtarianpour; Muhammad Reza Esmaili Givi (تحقیقات کاربردی علوم جغرافیایی)
Geographical studies on food categorized in five scales; global and transnational, national and regional, urban, rural and agricultural, domestic scales of food consumption and the individual as a consumer. Based on this categorization, the present study is placed within urban and domestic scales. By accepting that population of Tehran metropolis will definitely increase in future and regarding that based on systematic approach and limits to grow theory (Meadows, Randers, & Meadows, 2004), no growth in the world will continue forever. We must consider factors that limit the growth of Tehran, besides factors provoke development. One of the limiting factors is the natural and geographical potential of Tehran metropolis. For this research among qualitative methods in futures studies, we chose the scenario, because this method "make the future more real for decision makers to force new thinking and decisions". In the formulation of food consumption scenarios, due to the diversity of stakeholders, the challenges and the types of issues and ambiguities, the approach of the Global Business Network (GBN) was chosen. To analyze the key factors and identifying the key variables the structural analysis method and MickMac software was used. Based on two key variables, technology, and consumer responsibility, four scenarios were created, these are four scenarios: Smart eating scenario, McDonaldization of Society scenario, Food Geography scenario, and Community Eating scenario. In this study, four alternative food futures have been presented for Tehran. In these scenarios, both desirable and undesirable futures are clearly and accurately depicted. The geography of food scenario due to the neglect of the environmental capacities and natural and geographic potentials is the most unsustainable scenario for the future of Tehran. Without scenarios, thinking about the futures of food in Tehran is very difficult and even impossible. These scenarios can help us take into account possible futures in today's decisions. Although this article does not predict a specific future for food in Tehran, But, given the recognition and sensitivity of the events, it can be very useful for long-term decisions.